The green thread : dialogues with the vegetal world - Vieira, Patricia; Gagliano, Monica; Ryan, John (Ecocritical theory and practice., 2015)
The Green Thread is an interdisciplinary collection of essays that takes the risk of departing from the long-standing human perception of plants-defined by what they are thought to lack, including autonomy, agency, consciousness, and, arguably, intelligence-to explore new territories where the re-conceptualization of vegetal beings as active agents in social and cultural environments becomes possible.